Maternal smoking during pregnancy and offspring risk of intellectual disability: a UK-based cohort study - Madley-Dowd, Paul; Thomas, Richard; Boyd, Andy; Zammit, Stanley; Heron, Jon; Rai, Dheeraj (Frontiers in Psychiatry, 2024)
Background Observational studies have described associations of maternal smoking during pregnancy with intellectual disability (ID) in the exposed offspring. Whether these results reflect a causal effect or unmeasured confounding is still unclear. Methods Using a UK-based prospectively collected birth cohort (the Avon Longitudinal Study of Parents and Children) of 13,479 children born between 1991 and 1992, we assessed the relationship between maternal smoking at 18 weeks’ gestation and offspring risk of ID, ascertained through multiple sources of linked information including primary care diagnoses and education records. Using confounder-adjusted logistic regression, we performed observational analyses and a negative control analysis that compared maternal with partner smoking in pregnancy under the assumption that if a causal effect were to exist, maternal effect estimates would be of greater magnitude than estimates for partner smoking if the two exposures suffer from comparable biases. Results In observational analysis, we found an adjusted odds ratio for ID of 0.75 (95% CI = 0.49–1.13) for any maternal smoking and 0.97 (95% CI = 0.71–1.33) per 10-cigarette increase in number of cigarettes smoked per day. In negative control analysis, comparable effect estimates were found for any partner smoking (OR = 0.94; 95% CI = 0.63–1.40) and number of cigarettes smoked per day (OR = 0.94; 95% CI = 0.74–1.20). Conclusions The results are not consistent with a causal effect of maternal smoking during pregnancy on offspring ID.